A Physics-Based Simulation of Fluid–Solid Coupling Scenarios in an Ocean Visual System - Yiding Wang; Hongxiang Ren; Xiao Yang; Delong Wang (Journal of Marine Science and Engineering)
In the domain of ocean engineering, the authenticity of visual systems is a major challenge in developing marine simulators. A simulation strategy based on the smoothed particle hydrodynamics (SPH) simulation method is proposed in this study to enhance the realism of fluid–solid coupling scenes in a marine simulator visual system. Based on the SPH method, the water particles are constrained in each iteration according to the two physical fields of velocity divergence and density by setting an intermediate velocity. In the simulation of the fluid–structure interaction scenario, the contribution of the volume of the rigid model to the water particles is represented by a spatial map and then incorporated into the calculation of the pressure from the water particles according to the positional relationship between the water particles and the boundary. This strategy can effectively ensure the realism of the interaction between the rigid body and the waves on the one hand and significantly improve the speed of the marine simulator visual system on the other. The experiments show that this strategy can effectively save a significant amount of time and provide theoretical and technical references for enhancing the realism of a marine simulator visual system.